Stabilizing periodontally compromised teeth with braided glass fiber splint: A Case Report (International Journal of Food and Nutritional Sciences, 2022)
Plaque is a significant factor that leads to periodontal disease. One of the most common areas for plaque accumulation is the lower anterior region.Accumulation of plaque leads to periodontal disease progressionthatfurther leads to pathological tooth mobility which can result from acute periodontal inflammation and bone loss .Increased mobility can cause inconveniences for the patient. The new classification of periodontal disease states that teeth with progressive mobility may require splinting therapy to improve patient comfort and additional improvement for the Oral Health-related Quality of Life.Objective: To describe the correction of tooth mobility with Extracoronal fiber splint to improve function and comfort.Case report: The 39-year-old male patient presented with a chief complaint of mobile lower anterior teeth. At the intraoral examination, we noted gingival recession and loss of the interdental papilla, but without periodontal pocket. The tooth mobility test showed grade 2 mobility in 31,32, 41 and 42. The treatment plans of periodontal therapy begins with the initial phase, followed by the correction and the maintenance phases. In the initial phase, SRP(Scaling and Root planning) was done followed by extracoronal fiber splint placement to stabilize the mobile teeth.Conclusion: The splint does the redistribution of forces on the affected teeth, and also it minimizes the impact of the loss of support.